Appendiceal cancer in pregnancy and circulating tumor cells detection in the umbilical cord - Risa Kudo; Kensuke Matsumoto; Tatsuya Ishiguro; Tomoyuki Sekizuka; Koji Nishijima; Takayuki Enomoto; Kosuke Yoshihara (Heliyon)
Although malignant tumors metastasizing to infant or the placenta are occasionally reported during pregnancy, the adverse effects of maternal malignant tumors on fetus have not been clarified. Due to the rarity of appendiceal cancer during pregnancy, the adverse effects of tumor on pregnancy have not been clarified. Herein, we report a 30-year-old woman who experienced appendiceal cancer (stage IVC) wherein metastatic ovarian tumor was detected during pregnancy. A bilateral salpingo-oophorectomy and partial resection of the omentum were performed at 25 weeks 6 days gestational age (GA), followed by Cesarean section at 30 weeks 1 day GA. Postpartum chemotherapy with fluorouracil, oxaliplatin, and levofolinate calcium could not sufficiently control her disease. Purpura was observed all over the infant body at birth. The neonatal disseminated intravascular coagulation score was 4 according to the scoring system used by the Japanese Society of Obstetrical, Gynecological & Neonatal Hematology, which meet the neonatal disseminated intravascular coagulation criteria. Detailed histopathological examination did not detect any cancer cells in the placenta or umbilical cord. Moreover, no other malignant abnormalities were found based on comprehensive medical evaluation of the infant. However, maternal circulating tumor cells (CTCs) were detected in both maternal and umbilical cord blood samples from the patient. Collectively, this case might be the first step into studying the circulation of CTCs through the umbilical cord via placenta and its effects on the fetal outcome; maternal malignant tumor worsened the fetal condition. More advanced analysis of CTCs in umbilical cord blood would be useful for predicting negative effects of maternal malignant tumor on infant in future.